2004
DOI: 10.1111/j.1365-2222.2004.02084.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported prevalence and risk factors of asthma among Korean adolescents: 5‐year follow‐up study, 1995–2000

Abstract: SummaryObjectives The International Study of Asthma and Allergies in Childhood (ISAAC) questionnaires have shown that the prevalence of childhood asthma is increasing worldwide. Although Asian countries used to have lower prevalence rates of allergic disease than Western countries, this prevalence is increasing in several Asian countries. To determine whether the prevalence of childhood asthma is changing in Korean adolescents, we compared findings from nationwide cross-sectional surveys in 1995 and 2000 on po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 29 publications
4
87
2
2
Order By: Relevance
“…BMI was found to be a risk factor for asthma in the 2005 survey, but not in the 1997 survey. Many studies have shown that there is a positive correlation between obesity or BMI and asthma [21][22][23]. Our findings agree with other studies, showing that BMI is going to be an important risk factor for asthma in Turkish children.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…BMI was found to be a risk factor for asthma in the 2005 survey, but not in the 1997 survey. Many studies have shown that there is a positive correlation between obesity or BMI and asthma [21][22][23]. Our findings agree with other studies, showing that BMI is going to be an important risk factor for asthma in Turkish children.…”
Section: Discussionsupporting
confidence: 92%
“…Family history of atopic disease and living with a dog or cat were important risk factors for the development of asthma in both the 1997 and 2005 surveys. It is well known that asthma symptoms are triggered by animal allergens [21]. It has been observed that a family history of atopic disease constitutes an important factor in the genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…The first phase investigated the prevalence of allergic diseases and of related symptoms; the second phase investigated risk factors affecting the prevalence of asthma; and the third phase investigated prevalence at least five years after the previous stages [5]. In South Korea (hereafter Korea), same methodological studies were conducted in 1995 [6], and 2000 [7]. Following the study in 2000, an additional epidemiological survey was conducted on a nationwide scale in 2010 [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…26) The questionnaire consists of three main sections: 1) general characteristics including names, sex, date of birth, height, and weight; 2) a history of symptoms related to asthma, allergic rhinitis, AD, allergic conjunctivitis and food allergy; and 3) exposure to environmental factors associated with allergic disease. The Korean version of the ISSAC questionnaire was completed by parents or guardians of the preschool children.…”
Section: Isaac Questionnaire and Scoring Atopic Dermatitis Indexmentioning
confidence: 99%